Clinique de l'activité et formation de maîtres : le rôle de l'intervenant - Daniela Dias dos Anjos (Nantes Université, 2015)
This paper proposes a reflection on the role of the researcher in the clinic of activity when applied to the field of education. After reviewing the principles and procedures of this methodology, it analyzes the results of a research on public school teachers in the state of Sao Paulo (Brazil) who used this theoretical framework. It then examines how the fact that such intervention was rooted in the field of education impacted the researcher's activity and her reflections on her own work.